Analisa Efisiensi Economizer Terhadap Boiler (Gas Dan Solar) Di PT. Spindo III, Tbk - Finus Ainun; Jamaaluddin Jamaaluddin (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2018)
The role of boiler machines at PT. SPINDO in the galvanize pipe production process is very important, where the steam produced by the fire tube boiler machine is directly distributed into the blow system for the cleaning of the remaining galvanic in the pipe and heating the water for pipe washing. To determine the efficiency of the boiler, a direct method is used to analyze the efficiency of boiler machines and indirect methods as a way of calculating the amount of efficiency if an economizer is installed. The efficiency of diesel-fueled boilers using the direct method yields an average yield of 40.7% (forty point seven percent) and 45.84% (forty five point eighty four percent) for gas-fired boilers. However, by using an indirect method, efficiency if installed economizer is obtained at 85.55% (eighty five point fifty five percent) for diesel-fueled boilers with a capacity of 5 tons and 81.76% (eighty one point seventy six percent) of the efficiency of a gas-fired boiler with a capacity of 2 (two) tons. Efficiency improvements can also be done in many ways, including maintenance of a good and scheduled boiler machine for good boiler feed water treatment.